Consequential Surgeries Limit Recurrence of Skin Malignancies in Xeroderma Pigmentosum: A Case Report - Kurnia, Ahmad; Kartini, Diani; Herwirastri, Novinda; Adyasa, Zoya M (UI Scholars Hub, 2021)
Xeroderma Pigmentosum (XP) is a rare inherited skin malignancy with no causative treatment options. Reporting a 23-year-old woman with xeroderma pigmentosum who underwent several surgical tumor removals followed by further five procedures to apply tissue expander, facial resurfacing using full-thickness skin grafts with a donor from abdominal. The next series was tumor resection in the chin, forehead, nasal reconstruction, tumor removal on bilateral third digits, and defect closure. No recurrence after nine years of postoperative monitoring with an aesthetically acceptable result.